Сhest pain: a modern review of pain medicine - Anikeіeva Tetyana; Moisieienko, Anastasiya (Pain medicine, 2022)
Abstract. Background. Approximately 1% of all reasons for visits to primary care physicians are chest pain, and in 2–4% of these patients pain is the cause of potentially life-threatening cardiovascular disease. For a correct and quick diagnosis, it is extremely important that the clinician and the patient speak “one language”: the described complaints should be interpreted quickly and correctly, and the doctor’s questions should be clear to the patient. It is very important to get information from the patient about any accompanying symptoms and a detailed description of chest discomfort. History taking and physical examination should take the minimum amount of time required. That is why it is necessary to understand how and why conditions develop, the manifestation of which is pain in the chest. To highlight the significant variability of clinical manifestations of thoracalgia, mechanisms of development and features of clinical and laboratory-instrumental diagnosis of the causes of chest pain is a main aim of the review. Materials and methods. Modern foreign guidelines for the management of patients with chest pain, written in English, were used. Conclusions. After injuries, chest pain is the main reason of patients visits to the admission department for urgency care. Longstanding classification of the chest pain causes divides it into cardiac and non-cardiac, and cardialgia, in turn, can be subdivided to pain, caused by ischemic changes in the myocardium, and the one with a non-ischemic origin. Patients often do not use the term “pain” to describe their symptoms, but often use other terms such as discomfort, compression, or may associate discomfort with indigestion. When chest pain is caused by ischemia or insufficient coronary blood flow, it is called ischemic thoracalgia. Detection of angina pectoris is one of the main problems in the examination of patients with chest pain, and thoracalgia, which clinically and instrumentally correlates with acute angina pectoris, requires urgent diagnosis and treatment, as it may be a sign of acute coronary syndrome (ACS). Thoracic pain can not only affect the heart muscle, but also radiate from other anatomical areas or be felt secondarily, if it develops in an adjacent anatomical area (eg, thoracic spine, epigastric pain, etc.). Both acute and chronic chest pain should be carefully evaluated by a clinician, and further examination may be performed based on his findings. Appropriate and necessary laboratory and instrumental examination of patients, taking into account all possible risks, not only allows to quickly establish an accurate diagnosis, but also leads to more effective treatment.